2018 IEEE 7th Global Conference on Consumer Electronics (GCCE) 2018
DOI: 10.1109/gcce.2018.8574648
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Intra-Prediction in HEVC

Abstract: The use of machine learning techniques for encoding complexity reduction in recent video coding standards such as High Efficiency Video Coding (HEVC) has received prominent attention in the recent past. Yet, the dynamically changing nature of the video contents makes it evermore challenging to use rigid traditional inference models for predicting the encoding decisions for a given content. In this context, this paper investigates the resulting implications on the coding efficiency and the encoding complexity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The time spent during the encoding process to collect sequence-specific data hinders the encoding time reduction achieved in the latter. On the other hand, online-trained probabilistic models demonstrate less Bjøntegaard Delta Bit Rate (BDBR) [50] losses since the CU split decisions made in general are content-adaptive and relevant to the video content that is being encoded [49].…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time spent during the encoding process to collect sequence-specific data hinders the encoding time reduction achieved in the latter. On the other hand, online-trained probabilistic models demonstrate less Bjøntegaard Delta Bit Rate (BDBR) [50] losses since the CU split decisions made in general are content-adaptive and relevant to the video content that is being encoded [49].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…However, it has been shown that offline trained generic models may not perform well with the dynamics of the video content. Thus, content specific CU split likelihood models are important to achieve a higher prediction accuracy [49]. Therefore, this section describes an online prediction model (that acts alongside the offline SVM prediction models) that can keep the CU split decision prediction content-adaptive.…”
Section: Cu Split Decision Classification Using Probabilistic Momentioning
confidence: 99%
“…And the ration helps deciding the splitting decision of the CU. Buddhiprabha Erabadd et al (2018) [5] proposed a support vector machine-based solution to complexity reduction. They studied the online as well as offline model training of SVM and reported that off line training performs better in terms of time saving.…”
Section: Literature Surveymentioning
confidence: 99%